PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN MELALUI KOMITMEN ORGANISASI DI DIVISI CABLE & HARNESS PT. OSI ELECTRONICS BATAM - Alfa, Tomi; Utami Ady, Sri; Syaidah, Nur (CV. Lafadz Jaya, 2024)
This study evaluates the impact of transformational leadership on employee performance, with organizational commitment serving as a mediating variable within the Cable & Harness division of PT OSI Electronics Batam. A quantitative approach was employed, utilizing data collection through Likert-scale questionnaires and analyzed using multiple linear regression with SPSS version 29. The research population comprised 175 employees, with a sample size of 122 selected using the Slovin formula and stratified random sampling based on gender demographics. The findings indicate that transformational leadership has a positive and significant effect on organizational commitment (β = 0.814, t = 8.456, p < 0.05). Furthermore, organizational commitment positively and significantly influences employee performance (β = 0.443, t = 4.012, p < 0.05). The Sobel test confirmed that organizational commitment mediates the relationship between transformational leadership and employee performance (t = 5.916 > 2.040 at α = 5%). This research highlights the crucial role of transformational leadership and strong organizational commitment in fostering an effective work environment. The findings provide strategic insights for the management of PT OSI Electronics Batam to enhance operational efficiency and performance in the Cable & Harness division, as well as to develop strategies aimed at strengthening employee commitment and implementing effective transformational leadership practices.